Sons of Concubines and the Politics of Succession: Power, Lineage, Gender, and the Education of Abbasid Elites - Mujiburrohman; Alqarny, Ficky Uwais; Hannan, Haukil; Nur Rochbani, Ita Tryas; Dusturiyah, Mega; Azad, Inamul (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article investigates the disproportionate prevalence of caliphs born to umm al-walad, concubines who bore sons to Abbasid rulers, compared to those born of legal wives (al-nisāʾ al-maḥāʾir) in the early Abbasid caliphate. Drawing on classical historiographical sources and prosopographic data on thirty-seven Abbasid caliphs, this study explores the political logic behind this pattern. Rather than viewing this as a biological coincidence, the paper argues that it reflects a deliberate strategy of dynastic consolidation, privileging sons of concubines as more politically neutral, malleable, and free from tribal or aristocratic maternal affiliations. The article applies gender analysis, nasab theory, and Foucauldian discourse theory to show how the caliphate reproduced power not only through law and bloodline, but through narrative and institutional control. Ultimately, it reframes the role of umm al-walad not as passive bearers of lineage, but as embedded figures in the machinery of power, whose sons embodied the ideal of state-dependent, non-tribal leadership. The study highlights how historiography served as an instrument of legitimizing these choices, challenging normative assumptions about lineage, legitimacy, and gender in early Islamic political thought. This study also contributes to Islamic educational studies by showing how caliphal succession functioned as a site of political pedagogy, where power, obedience, and legitimacy were cultivated through maternal education and courtly socialization.